Marketing Mix Modeling a Bayesian Approach to Assess Advertising Effectiveness on Website Traffic Volume - Peixoto, Ricardo de Carvalho Lourenço Beirão (2023)
Project Work presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science